Development Of Olericulture Seed Cultivation Program Guidebook As An Effort To Improve Students' Industrial Agriculture Insights - Melisa Putri Febriyanti,; Rissa Lusiyana Safitri ,; Tika Widiya Ningrum ,; Lia Silvira ,; Gelang Arum Kemangi Sukma ,; Lailatul Nuraini , (Jurnal Serambi Ilmu, 2024)
This study aims to assess the validity of the program guidebook in improving students' industrial agricultural insights through training in cultivation of olericultural plants. The research method used is research and development with the ADDIE development model. The ADDIE development stage consists of the analysis stage (analysis), the planning stage (design), the development stage (development), the implementation stage (implementation), and the evaluation stage (evaluation). The data analysis technique used was descriptive quantitative, with the data collection method using a validation questionnaire. The results of the guidebook validation show that the total percentage of all aspects of the three validators is 83.75%. This shows that the results of the eligibility criteria for the program guidebook that has been prepared are in the very feasible category and can then be implemented in community service activities regarding the olericulture cultivation program to improve students' industrial agricultural insights.